فاعلية استخدام الكتيب الإلكتروني التفاعلي في تعلم بعض مهارات الباليه - أمين، وسام عادل السيد (جامعة حلوان - كلية التربية الرياضية للبنين, 2021)
أستهدف البحث تصميم كتيب إلكتروني لتعلم بعض مهارات البالية لطالبات الفرقة الثالثة بكلية التربية الرياضية جامعة مدينة السادات، ومعرفة تأثيره على مستوى الأداء الفني لبعض مهارات الباليه (الجراند ايشابية-البالونية الديفلوبية أماما-الديفلويية جانبا-الديفلوبية خلفا)، واستخدمت الباحثة المنهج التجريبي على عينة قوامها (٢٨) طالبة بالفرقة الثالثة بكلية التربية الرياضية-جامعة مدينة السادات تم تقسيمهن إلى مجموعتين أحداهما مجموعة تجريبية، والأخرى مجموعة ضابطة قوام كل منهما (١٤) طالبة، ومن أدوات البحث: اختبارات بدنية-تقييم مستوى أداء بعض مهارات الباليه-اختبار الذكاء العالي-الكتيب الإلكتروني التفاعلي، واستخدمت الباحثة الأساليب الإحصائية التالية: المتوسط الحسابي-الانحراف المعياري-الوسيط-معامل الالتواء-معامل الارتباط البسيط-اختبار ""ت"" – نسب التحسن، ومن أهم النتائج: 1-يؤثر استخدام الكتيب الإلكتروني التفاعلي تأثيرا إيجابيا دال إحصائيا عند مستوى (0.05) على مستوى الأداء الفني لبعض مهارات الباليه (الجراند ايشابية-البالونية-الديفلوبية أماما-الديفلوبية جانبا-الديفلوبية خلفا) لطالبات الفرقة الثالثة بكلية التربية الرياضية-جامعة السادات. 2-يؤثر أسلوب التعلم بالأوامر تأثيرا إيجابيا دال إحصائيا عند مستوى (0.05) على مستوى الأداء الفني لبعض مهارات الباليه (الجراند ايشابية-البالونية-الديفلوبية أماما-الديفلوبية جانبا-الديفلويية خلفا) لطالبات الفرقة الثالثة بكلية التربية الرياضية-جامعة السادات. ٣- زيادة فاعلية الكتيب الإلكتروني التفاعلي عن أسلوب التعلم بالأوامر في التأثير إيجابيا (القياس البعدي) على مستوى الأداء الفني لبعض مهارات الباليه قيد البحث. 4- تفوق أفراد المجموعة التجريبية على أفراد المجموعة الضابطة في نسب تحسن القياس البعدي عن القبلي في مستوي أداء بعض مهارات الباليه قيد البحث."
The research aimed to design an electronic booklet to learn some ballet skills for students of the third year at the Faculty of Physical Education-Sadat University, and to know its effect on the level of technical performance of some ballet skills (Grand Ishia-Balloon-in front-Devlopia on the side- Devlopian in front). They consist of (28) female students in the third division of the College of Physical Education-Sadat City University. They were divided into two groups, one of which is an experimental group, and the other is a control group of (14) students, The research tools include: physical tests -assessing the performance level of some ballet skills-high intelligence test-interactive electronic handbook. The researcher used the following statistical methods: arithmetic mean-standard deviation-median-torsion coefficient- simple correlation coefficient- ""T"" test-ratios Improvement. Among the most important results: 1-The use of the interactive electronic booklet has a positive and statistically significant effect at the level of (0.05) on the technical performance of some ballet skills (Grand Ishabia-Balloon-Divelopé in front-Devlopé on the side- Devlopé on the back) for students of the third year of the Faculty of Physical Education-Sadat University. 2- The command learning method has a statistically significant positive effect at the level of (0.05) on the level of technical performance of some ballet skills (Grand Ishia-Balloon-Divelopé in front-Divelopia on the side- Divelopia on the back) for students of the third year of the Faculty of Physical Education - Sadat University. 3-Increasing the effectiveness of the interactive electronic booklet on the method of learning by commands in positively influencing (telemetry) on the technical performance level of some ballet skills under consideration. 4-The members of the experimental group outperformed the control group members in the percentage of improvement of the post-tribal measurement in the level of performance of some ballet skills under study."
Keywords: الكتيب الإلكتروني -- رياضة الباليه -- المهارات الفنية -- التربية الرياضية